Makna Strategis Selat Lombok dan Perkembangannya Sebagai Jalur Pelayaran Internasional - Rustam, Ismah (Global and Policy Journal of International Relations, 2018)
ABSTRACTAs an island nation that connects two oceans, Indonesia has several important choke points scattered in several points including the Malacca Strait, Sunda Strait, Lombok Strait and Makassar Strait. Lombok Strait is one of the international trade routes and the southern entrance for the shipping of ships from various countries. In addition, this strait has more privileges for storing the wealth of marine biota and tourism economic resources are quite manageable. The strategic significance of the Lombok Strait encourages the government to make appropriate policies regarding regulation and utilization. Given the Lombok Strait has a strategic meaning also for major countries such as Australia, China and the United States. Indonesia should be able to protect its economic, political and security interests within its sovereign territory. This paper will examine the challenges and opportunities faced by the Indonesian government on the Lombok Strait as an international shipping lane and how the current security system of the Lombok Strait. In addition, we will discuss the application of Particularly Sensitive Sea Area (PSSA) idea in providing special protection and plan to arrange international shipping line with Traffic Separation Scheme in Lombok Strait.Keywords: Lombok Strait, International Shipping, Indonesia, ocean securityDOI: https://doi.org/10.33005/jgp.v6i01.1884